The role of the right posterior parietal cortex in letter migration between words. - Cazzoli, D; Müri, R; Kennard, C; Rosenthal, C (MIT Press Journals, 2015)
When briefly presented with pairs of words, skilled readers can sometimes report words with migrated letters (e.g., they report hunt when presented with the words hint and hurt). This and other letter migration phenomena have been often used to investigate factors that influence reading such as letter position coding. However, the neural basis of letter migration is poorly understood. Previous evidence has implicated the right posterior parietal cortex (PPC) in processing visuospatial attributes and lexical properties during word reading. The aim of this study was to assess this putative role by combining an inhibitory TMS protocol with a letter migration paradigm, which was designed to examine the contributions of visuospatial attributes and lexical factors. Temporary interference with the right PPC led to three specific effects on letter migration. First, the number of letter migrations was significantly increased only in the group with active stimulation (vs. a sham stimulation group or a control group without stimulation), and there was no significant effect on other error types. Second, this effect occurred only when letter migration could result in a meaningful word (migration vs. control context). Third, the effect of active stimulation on the number of letter migrations was lateralized to target words presented on the left. Our study thus demonstrates that the right PPC plays a specific and causal role in the phenomenon of letter migration. The nature of this role cannot be explained solely in terms of visuospatial attention, rather it involves an interplay between visuospatial attentional and word reading-specific factors.